PERKAWINAN IN FIERI DAN PERKAWINAN IN FACTO ESSE DALAM PEMAHAMAN YURIDIS GEREJA KATOLIK - Galed, Daniel Ortega (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Dignity and marriage institutions with all kinds of complexity are always interesting to be discussed from any aspects. Marriage always has a permanent characteristic whether cultural influences or the mentality of the age changes in concepts and ideas in it. It demands the involvement of the subject (husband and wife) and requires the existence of